2008
DOI: 10.1016/s0091-679x(08)85019-4
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular Fluorescence Complementation: Visualization of Molecular Interactions in Living Cells

Abstract: A variety of experimental methods have been developed for the analysis of protein interactions. The majority of these methods either require disruption of the cells to detect molecular interactions or rely on indirect detection of the protein interaction. The bimolecular fluorescence complementation (BiFC) assay provides a direct approach for the visualization of molecular interactions in living cells and organisms. The BiFC approach is based on the facilitated association between two fragments of a fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 100 publications
1
111
0
Order By: Relevance
“…BiFC assays were performed as described (56). An improved BiFC assay with a high signal-to-noise ratio was selected to avoid background interference (57,58).…”
Section: Methodsmentioning
confidence: 99%
“…BiFC assays were performed as described (56). An improved BiFC assay with a high signal-to-noise ratio was selected to avoid background interference (57,58).…”
Section: Methodsmentioning
confidence: 99%
“…FSP27 was highly expressed in the fat cake (lane 1) and coimmunopre cipi tated with NFAT5 (lanes 3 and 5) but not when non immune IgG (lanes 2 and 4) was used for the immunoprecipitation, thus substantiating the physical with the N-terminal (VN173) or C-terminal (VC155) of Venus for the BiFC assay. If FSP27 and NFAT5 interact with each other, the interaction should bring VN173 and VC155 into close proximity and reconstitute an intact Venus molecule, which can be detected by direct visualization with fl uorescence imaging ( 21 ). To confi rm the interaction between the fusion proteins, we transiently expressed the proteins in HEK293 cells that had been loaded with fatty acids (FAs) to promote LD formation.…”
Section: Apoptosismentioning
confidence: 99%
“…The result also showed that the interaction took place in the nuclear (Figure 4). is that it enables characterization of protein-protein interactions in the natural cellular environment [5][6][7].…”
Section: Interaction Assay Of Ebna1 and Host Protein By Bimcmentioning
confidence: 99%
“…Bimolecular complementation (BiMC) assay is a useful approach method for the detection, visualization and map of protein-protein interactions in live mammalian cells [5]. In this system, the enhanced yellow fluorescent protein (EYFP) is split into N-and Cterminal fragments, and reconstitution of these two fragments takes place by the mediation of a proteinprotein interaction, thus resulting in irreversible fluorescent signal [6]. In order to improve our understanding of the interaction patterns of EBNA1 and host proteins, in this study, we established a BiMC assay system expressing a fusion protein of EBNA1 and the C-termini of EYFP, and this system was employed in the assay for a interaction detection of EBNA1 with one host protein in living 293T cells.…”
Section: Introductionmentioning
confidence: 99%